Sharia Financing in Improving the Ummah's Economy - Ika Safitri (Mandalika Institute, 2025)
Sharia financing is one of the important instruments in the modern economy, especially in the context of the people's economy. The basic concept of sharia financing that is free from elements of riba, gharar (uncertainty), and maysir (gambling), offers alternative solutions for Muslims in carrying out economic activities in accordance with sharia principles. In its development, sharia financing has proven to make a significant contribution to improving the welfare of the people, both through the micro, small, and medium (MSME) sector and other sectors. Through Islamic financial institutions, such as Islamic banks, Islamic cooperatives, and non-bank financial institutions, Islamic financing provides fairer and more transparent access to financing, as well as reducing economic inequality. Financing based on mudharabah, musharakah, murabahah, and ijarah, for example, encourages collaboration between capital owners and entrepreneurs, increases productivity, and creates wider employment. In addition, sharia products such as sukuk also play an important role in attracting beneficial investments for infrastructure development and increasing the economic capacity of the community. However, although sharia financing has great potential, challenges still exist, such as the lack of public understanding of sharia products, limited access to sharia financial institutions in certain regions, and challenges in creating a supportive ecosystem. Therefore, it is necessary to increase Islamic financial literacy, strengthen regulations, and support from the government and the community to optimize the role of Islamic financing in improving the economy of the people in a sustainable manner.